Pelatihan Seni Baca Al-Qur’an (Tilawah) untuk Semua Usia sebagai Upaya Mencetak Kader Qori Qori’ah di Kabupaten Trenggalek - Rizal, Rizal Furqan Ramadhan (Madani: Jurnal Pengabdian Ilmiah, 2024)
The art of reading the Qur'an is a science and skill that requires the ability to master the voice, song, and understanding of reading the Qur'an (tajwid and fashohah). In the modern era, qori qoriah is starting to erode with the times, especially in Trenggalek Regency. Qori and qoriah are skills for people who can recite the holy Qur'an using songs (naghom) without destroying or reducing the rules of reading the Qur'an (tajwid and fashohah). Several factors are related to the minimal number of qori and qoriah in Trenggalek Regency. So it is necessary to hold training in the art of reading the Qur'an or recitations in order to produce cadres or seeds of qori and qoriah from an early age. The method used is PAR (Participatory Action Research) based on service activities involving communities or organizations related to tilwatil qur'an training. The relevant organization is the Branch Leader of Jam'iyyatul Qurra' Wal Huffazh Nahdlatul Ulama Trenggalek Regency as well as a resource person. The PAR method starts with 5 cycles, including knowing, understanding, planning, acting, and changing. The five cycles have different procedures and are applied to this service. The results of this training were quite significant; the resource person took 4 random samples of participants to recite recitation material (practice). The four participants were able to perform the recitation of recitations quite well. From the results of this evaluation, the potential for more and Moriah in Trenggalek Regency can still be quite exiting and needs to be developed gradually.